Empirical study on relationship between corporate social responsibility and financial performance in Korea - Jae Joon Han; Hyun Jeong Kim; Jeongmin Yu (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2016)
There have been numerous studies on corporate social responsibility (CSR) and its relation to corporate performance. Recently, studies in this field have paid particular attention to the method of measurement in order to identify the CSR activities. One of the widely recognized measures to proxy CSR is the Environmental, Social, and Governance (ESG) score. This paper examines the relationship between Corporate Social Responsibility (CSR) and corporate profit by testing the ESG performance score on the firm's Financial Performance (FP), specifically for Korea Stock Market (KOSPI) listed firms in the period of 2008 ~ 2014. We use three separate individual Environmental, Social and Corporate Governance (ESG) disclosure scores from Bloomberg for the CRS proxy measure, as well as the Return on Equity (ROE), Market-to-Book Ratio (MBR) and Stock Return for the FP measures. We found that the ESG disclosure scores (the measures of environmental, social, and governance responsibility performance) in the Korean corporations shows diversified results. Particularly, the environmental responsibility performance score presents a negative (or U curve) relationship with FP, whereas the governance responsibility performance score presents a positive (or inverse U curve) relationship with FP. On the other hand, we did not find any statistically significant evidence of a relationship between the social responsibility performance score and FP.
Keywords: 650; Corporate social responsibility (CSR); Environmental; Social; Governance (ESG); Financial performance (FP); Sustainability